Effect of religious belief on informal reasoning about biotechnology issues - Pope, T.; Koul, Rekha; Dawson, V. (Australian Science Teachers Association, 2017)
The advances of modern biotechnology provide teachers with a number of opportunities to explore socioscientific issues, and in doing so to enhance students' reasoning skills. Although some attempt has been made to understand cultural differences in students' informal reasoning across international and regional boundaries, there is limited research about the differences that exist between students who identify with a Christian worldview and those students who do not. To investigate the role that students' religious beliefs played in their informal reasoning about biotechnology issues regarding genetically modified food, genetic screening, therapeutic cloning and reproductive cloning, the written responses of 101 students identified as accepting a Christian worldview was compared with 21 students who did not identify with a Christian worldview. Using a qualitative approach, the students' responses to these issues were analysed to identify the modes of informal reasoning incorporated in the justification of their views about the technology. It was shown that students with a higher degree of religious belief demonstrated less use of rational reasoning and a greater reliance on intuitive reasoning in their responses to socioscientific issues when compared with their less-religious peers. The findings highlight the need for initiatives that will develop students' rational and emotive reasoning and encourage them to acknowledge the presuppositions of their belief system and how these influence their attitudes towards controversial issues in science.